(untitled) (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2017)
Examining chitosan’s antioxidant potential using well-established in vitro systems including DPPH and superoxide (O2- )/hydroxyl (-OH) radical scavenging. At concentrations between 0.125 and 1.0mg/ml, the reducing capacity varied from 15.47% to 19.00%. Concentrations of chitosan (0.125–1.0mg/ml) exhibited a scavenging capability for 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radicals ranging from 28.37% to 38.03%. Chitosan’s (0.125-1.0 mg/ml) ability to scavenge hydroxyl radicals varied between 12.20% and 40.10%. The concentration of the superoxide anion radical varied from 15.20% to 32.10% between 0.125 and 1.0 mg/ml. Overall, chitosan showed promising antioxidant action, suggesting its application as a dietary supplement or medicinal component. Last but not least, chitosan’s ability to scavenge and to reduce rose as its concentration did.